Characteristics of exopolysaccharides produced by isolates from natural bioflocculant of Ruditapes philippinarum conglutination mud - Feng, Lijuan; Qian, Tingting; Yang, Guangfeng; Mu, Jun (Frontiers in Microbiology, 2023)
Three novel types of exopolysaccharides (EPS) EPS-S8, EPS-S5 and EPS-F10 were extracted and purified from bacterial isolates Bacillus sp. GHS8, Pseudoalteromonas sp. GHS5 and Psychrobacter sp. GHF10, which were originated from natural bioflocculant of Ruditapes philippinarum conglutination mud (RPM), respectively. The EPS had similar function groups C-H, N-H, C-O and C=O with three or more different monosaccharide compositions of neutral sugars and amino sugars. These EPS contained 5-7 types of glycosidic linkage, and EPS-S8 had the simplest glycosidic linkage types and exhibited the lowest level of molecular weights (Mw,166 kDa). Three types of EPS all showed higher peak flocculation activities than the reported crude EPS from the RPM. Besides, the EPS also exhibited efficient decoloration and antioxidation activities. Especially, EPS-S8 had better performance of decoloration activity and hydroxyl radicals scavenging ability due to the low Mw, simple monosaccharide composition and glycosidic linkage types.